Assessment and management of adverse effects of pediatric chemotherapy treatment: an integrative review (Research, Society and Development, 2022)
The main therapy for the treatment of childhood and adolescent cancer is chemotherapy and its most frequent adverse effects are: pain, fatigue, apathy, loss of appetite, weight loss, alopecia, hematomas, bleeding, mucositis, nausea, among others. And the objective of this study was to identify in the literature the role of nurses facing the most common adverse effects of pediatric chemotherapy treatment, and for this, an integrative review of the literature was conducted in the period from January 2010 to February 2022, being included 21 productions in full. Chemotherapy promotes a series of physical, emotional and transformations in routine for children and adolescents. The studies show that approximately 80% of these patients had symptoms that classify as severe and very severe. Pain is common and persistent, and was the most frequently mentioned symptom among the studies, followed by fatigue. The long treatment journey makes it the nurse's mission to encourage and help patients and their families to overcome adversities, and to promote compliance and continuity of treatment, guiding good practices to deal with adverse events, awakening a sense of comfort and safety. All adverse effects of chemotherapy treatment can be properly managed by nursing professionals aiming to provide a less traumatic treatment, with control and relief of symptoms pharmacologically or through alternative therapies, and promoting an emotional support to families.